(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
The so called ‘Editorial Philology’ has recently been considered as a category of Modern Philology, in particular a sub-category of 20th Century Philology. In this paper some considerations about the relationship between Texts, Collections and Complete Works, during the transition from paper to digital, are suggested.